A closer look at the deep radio sky: Multi-component radio sources at 3 GHz VLA-COSMOS - E. Vardoulaki; E. F. Jiménez Andrade; A. Karim; M. Novak; S. K. Leslie; K. Tisanić; V. Smolčić; E. Schinnerer; M. T. Sargent; M. Bondi; G. Zamorani; B. Magnelli; et al. (EDP SCIENCES S A, 2022)
Context. Given the unprecedented depth achieved in current large radio surveys, we are starting to probe populations of radio sources that have not been studied in the past. However, identifying and categorising these objects, differing in size, shape and physical properties, is becoming a more difficult task.Aims. In this data paper we present and characterise the multi-component radio sources identified in the VLA-COSMOS Large Project at 3 GHz (0.75 arcsec resolution, 2.3 mu Jy beam(-1) rms), i.e. the radio sources which are composed of two or more radio blobs.
Methods. The classification of objects into multi-components was done by visual inspection of 351 of the brightest and most extended blobs from a sample of 10,899 blobs identified by the automatic code BLOBCAT. For that purpose we used multi-wavelength information of the field, such as the 1.4 GHz VLA-COSMOS data and the Ultra Deep Survey with the VISTA telescope (UltraVISTA) stacked mosaic available for COSMOS.
Results. We have identified 67 multi-component radio sources at 3 GHz: 58 sources with active galactic nucleus (AGN) powered radio emission and nine star-forming galaxies. We report eight new detections that were not observed by the VLA-COSMOS Large Project at 1.4 GHz, due to the slightly larger area coverage at 3 GHz. The increased spatial resolution of 0.75 arcsec has allowed us to resolve (and isolate) multiple emission peaks of 28 extended radio sources not identified in the 1.4 GHz VLA-COSMOS map. We report the multi-frequency flux densities (324 MHz, 325 MHz, 1.4 GHz & 3 GHz), star formation rates, and stellar masses of these objects. We find that multi-component objects at 3 GHz VLA-COSMOS inhabit mainly massive galaxies (>10(10.5)M(circle dot)). The majority of the multi-component AGN lie below the main sequence of star-forming galaxies (SFGs), in the green valley and the quiescent region. Furthermore, we provide detailed descriptions of the objects and find that amongst the AGN there are two head-tail, ten corelobe, nine wide-angle-tail (WAT), eight double-double or Z-/X-shaped, three bent-tail radio sources, and 26 symmetric sources, while amongst the SFGs we find the only star-forming ring seen in radio emission in COSMOS. Additionally, we report a large number (32 out of 58) of disturbed/bent multi-component AGN, 18 of which do not lie within X-ray groups in COSMOS (redshift range 0.08 <= z < 1.53).
Conclusion. The high angular resolution and sensitivity of the 3 GHz VLA-COSMOS data set give us the opportunity to identify peculiar radio structures and sub-structures of multi-component objects, and relate them to physical phenomena such as AGN or star-forming galaxies. This study illustrates the complexity of the mu Jy radio-source population; at the sensitivity and resolution of 3 GHz VLA-COSMOS, the radio structures of AGN and SFG both emitting radio continuum emission, become comparable in the absence of clear, symmetrical jets. Thus, disentangling the AGN and SFG contributions using solely radio observations can be misleading in a number of cases. This has implications for future surveys, such as those done by square kilometre array (SKA) and precursors, which will identify hundreds of thousands of multi-component objects.